Stephen A. Douglas papers - Douglas, Stephen A. (Stephen Arnold), 1813-1861.; Douglas, Stephen A. (Stephen Arnold), 1813-1861.
Pamphlet titled, "Address of the Hon. Stephen A. Douglas, at the annual fair of the New York State Agricultural Society," published in 1851, pertaining to agriculture in the United States; newspaper clipping of Douglas's speech (12 June 1857; Springfield, Ill.) concerning the Kansas question, the Dred Scott decision, and Utah; and list (circa 1934) of Douglas's correspondents in the Stephen A. Douglas papers in the University of Chicago Library.
In part, negative photocopy from originals in private hands.
Private
U.S. senator and representative from Illinois, public official of Illinois, and jurist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Scott, Dred, -- 1809-1858 -- Trials, litigation, etc; Agriculture -- United States; Slavery -- United States; Kansas -- Politics and government -- 1854-1861.; United States -- Race relations; Utah -- Politics and government; Jurists; Public officials -- Illinois; Representatives, U.S. Congress -- Illinois; Senators, U.S. Congress -- Illinois